Mechanisms of Bolt Preload Relaxation Arising from In-Plane Loads and Bolt Bending - Welch Michael (Journal of Mechanical Engineering, 2024)
Classical analysis methods have shown that flexural, in-plane, deflections due to shear strain in the flange pack of preloaded bolted joints produce bending moments and tensile loads on bolts within the joint. These bending moments and tensile loads are most noticeable in joints that are required to support large in-plane loads and torsional moments. The shear loads on the bolt associated with the flexural deflections can result in the bolt head, or nut, slipping relative to the flanges. This slippage will in turn result in mechanical loosening of the joint. The bending moments associated shear loads and tensile loads produced by the combination of both out-of-plane and in-plane external loads and torsional moments are in addition to the bolt preload. These additional loads, combined with a high initial bolt preload, can cause yielding of the bolt, which can also result in relaxation of the initial preload. This article reviews earlier work in determining the tensile bolt stresses induced in preloaded bolts by the external loads and presents methods of calculating the amount of preload relaxation that could occur from each mechanism discussed.